مولانا سید مناظر احسن گیلانی بحیثیت میلاد نامہ نگار؛ ایک تجزیاتی مطالعہ: Mawlana Manazir Ahsan Gilani as a Meelad Nama Nigar; An analytical Study - Rathore, Dr. Aman Ullah (Al-Amīr Research Journal for Islamic Studies, 2023)
It is a common contemporary practice to write “MeeladNamas”. Birth related stories of Hazrat Mohammad (ﷺ) in Moulana Gilani’s time. Moulana Manazir Ahsan Gilani (1892-1956) was a great author he worked almost in every sphere/departments of Islam. It would have out of question if he did not pick his pen on the topic of MeeladNama. So he wrote a book on the topic named ‘Zahoor E Noor’ (Naya Meelad Nama) which was an excellent example of his style of writing and collecting the information from related resources. According to some critics his resources and reference were not up to the mark; but his purpose to develop love and affection in the minds and hearts of whole Muslims was very beautifully made possible through this collection ‘Zahoor E Noor’. This article delve into scholarly discussion surrounds the comparison with other ‘Meelad Namas’ and also gives very useful information regarding stories and supernatural event of Hazrat Mohammad ﷺs’ birth. The events and supernatural things related to birth of Hazrat Mohammad ﷺ also shows greatness of Mohammad ﷺ and gives importance to his relations with God. Key Words: Holy Prophet ﷺ, Birth Related Stories, Manazir Ahsan Gilani, Meelad Nama, Zahoor Nama.